HEMIDESMUS INDICUS: EVALUATION OF ITS NOOTROPIC EFFECT IN MICE - SHETE R V; BODHANKAR S L (International Journal of Pharma and Bio Sciences, 2010)
Dementia is one of the age-related mental problems, and a characteristic symptom of Alzheimer’s disease. Nootropic agents are clinically used in situations where there is organic disorder in learning abilities and for improving memory, mood and behavior, but the resulting side-effects associated with these agents have made their utility limited. Ayurveda emphasizes use of herbs, nutraceuticals or lifestyle changes for controlling age related neurodegenerative disorders. The present study was undertaken to assess the potential of an ayurvedic rasayana (rejuvenator) drug Hemidesmus indicus roots as a memory enhancer. Elevated plus maze and passive avoidance paradigm were employed to evaluate learning and memory parameters. The chloroform and n-butanol fractions of ethanolic extract H. indicus root (3, 10 and 30 mg/kg, p.o.) were screened for claimed potential in mice. The n-butanol fraction of H. indicus extract significantly improved learning and memory at all doses mice. Hence, H. indicus might prove to be a useful memory restorative agent in the treatment of dementia seen in the Alzheimer’s disease.